2022
DOI: 10.3390/math10203819
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intangible Assets on the Market Value of Companies: Cross-Sector Evidence

Abstract: The impact of corporate intangibles on a company’s market value has been a widely debated topic. A large body of literature has separately examined the industry’s effect- or firm-specific attributes, such as industry type, company size, company age, or indebtedness and profitability, on the motivation to disclose information on intangible assets, but without considering a comprehensive view. This paper examines the role intangible assets play in a firm’s market valuation besides other firm-specific characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Roggeman et al (2012) elaborated that the current accounting methods used under the International Financial Reporting Standards (IFRS) require most intangibles to be expensed and, as a consequence, capitalized intangibles do not reflect how valuable intangible assets are for many companies. Dancaková et al (2022) argued that due to the persistent conservatism of the IFRS, the actual value of intangible assets cannot be fully recognized and disclosed in financial statements. Taking into consideration that various definitions of intangible assets are employed in the field of taxation, accountancy and transfer pricing of multinational companies, it is hypothesised that intangible assets are undervalued in financial statements.…”
Section: Resultsmentioning
confidence: 99%
“…Roggeman et al (2012) elaborated that the current accounting methods used under the International Financial Reporting Standards (IFRS) require most intangibles to be expensed and, as a consequence, capitalized intangibles do not reflect how valuable intangible assets are for many companies. Dancaková et al (2022) argued that due to the persistent conservatism of the IFRS, the actual value of intangible assets cannot be fully recognized and disclosed in financial statements. Taking into consideration that various definitions of intangible assets are employed in the field of taxation, accountancy and transfer pricing of multinational companies, it is hypothesised that intangible assets are undervalued in financial statements.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the resource-based theory, it is suggested that business groups are more likely to engage in acquisitions when moderated by high levels of intangible assets (Carabel et al, 2021). Therefore, when business groups possess a substantial amount of intangible assets, they are better equipped to pursue and manage diversified international acquisitions, leveraging their strategic resources to enter new markets and industries (Dancaková et al, 2022). These findings have important implications for businesses and investors.…”
Section: Strategic Asset Search Strengthens the Positive Relationship...mentioning
confidence: 99%
“…Hence, it helps the company consider its position in market competition and competitiveness (Aprilianda & Nur, 2023). It also can guide the manager in making strategic decisions to increase the company's worth (Dancaková et al, 2022). Hence, investigating the determinant of the firm value can benefit both the company and the investor.…”
Section: Introductionmentioning
confidence: 99%